A Synthetic View on Momilactones and Related 9β-H Pimarane Skeleton Diterpenoids - Zhang, Yue; Li, Mengran; Liu, Qichang; Huang, Jian; Chen, Yang (Frontiers in Chemistry, 2022)
Allelochemicals are secondary metabolites produced from plants and used to prevent and control the invasion of other plants and microorganisms, with broad application prospects in crop protection. Structurally, momilactones belong to 9β-H pimarane diterpenoids, one of rice’s significant allelochemicals with anti-weeds and antibacterial activity. Rare studies have been reported with the synthesis challenges of the unique 9β-H pimarane skeleton. Hence, synthetic strategies of momilactones and related 9β-H pimarane skeleton are reviewed from 1984 to 2021.